SCIENCE AND TECHNOLOGY PARKS AS A PROJECT OF THE ENLARGEMENT OF ENTREPRENEURSHIP AND INNOVATION OF THE WARMIŃSKO-MAZURSKIE VOIVODESHIP (Research Bulletins of the Faculty of Economic Sciences, 2019)
The Warmian-Masurian Voivodeship belongs to the least enterprising and innovative parts of Poland. The solution to the problem may be creation of science and technology parks. Three technology parks in the Warmia and Mazury voivodeship  have been formed in the most dynamically developing business centers (in Olsztyn, Elbląg and Elk). All of them offer access to their investment areas and conference rooms, as well as specialist consultancy. After several years of operation of three parks, it has been noticed that small innovative enterprises are located in the parks.
Keywords: science and technology parks, entrepreneurship, enterprise, business-related institutions, innovation